Analytic results for decays of color singlets to gg and qq¯ final states at NNLO QCD with the nested soft-collinear subtraction scheme - Caola, F; Melnikov, K; Röntsch, R (Springer Nature, 2019)
We present compact analytic formulas that describe the decay of colorless particles to both qq¯ and gg final states through next-to-next-to-leading order in perturbative QCD in the context of the nested soft-collinear subtraction scheme. In addition to their relevance for the description of decays like V→qq¯' , V=Z,W , H→bb¯ and H→gg , these results provide an important building block for calculating NNLO QCD corrections to arbitrary processes at colliders within the nested soft-collinear subtraction scheme.